COSMIC observation of stratospheric gravity wave and ionospheric scintillation correlation. (June 2021) - Wu, Qian; Chou, Min-Yang; Schreiner, W.; Braun, J.; Pedatella, N.; Cherniak, Iurii
Abstract: A correlation study is performed to investigate possible connections between the stratospheric gravity waves and the ionospheric plasma bubble induced GPS signal scintillations. Using the COSMIC 1 neutral temperature data (10–30 km), we extract gravity wave amplitudes with vertical wavelengths from 2.5 to 10 km within the latitudinal range from 37.5S to 37.5N. We then calculated the occurrence of high GPS L1 amplitude scintillation (S4 > 0.2) in the equatorial region (25S and 25N). The high S4 values showed consistent higher correlations with gravity waves at the equator than those away from the equator for all vertical wavelengths between 2010 and 2013. While the peak correlation is only ~0.2, the consistency over different wavelengths and years suggests a possible link, which could be through seeding of plasma bubbles and/or modulation of the neutral wind dynamo by gravity waves. We see the need for further study based on statistics of simultaneous observations of gravity waves, ionospheric scintillations, and other ionospheric and thermospheric parameters, which can lead to a better understanding of the plasma bubble formation mechanism. Highlights: GPS RO observations of stratospheric gravity waves and equatorial bubbles are analyzed to study gravity wave seeding effect. Gravity waves at the equator have the larger correction (0.2) with the bubbles compared to those away from the equator. This is a significant analysis of the gravity wave seeding effect on the global scale.